Effects of long-term exposure to the low-earth orbit environment on drag augmentation systems - Serfontein, Zaria; Kingston, Jennifer; Hobbs, Stephen; Holbrough, Ian E.; Beck, James C.; Impey, Susan A.; Aria, Adrianus Indrat (International Astronautical Federation (IAF), 2020)
Spacecraft in low-Earth orbit are exposed to environmental threats which can lead to material degradation and component failures. The presence of atomic oxygen and collisions from orbital debris have detrimental effects on the structures, thus affecting their performance. Cranfield University has developed a family of drag augmentation systems (DAS), for end-of-life de-orbit of satellites, addressing the space debris challenge and ensuring that satellites operate responsibly and sustainably. Deorbit devices are stowed on-orbit for the duration of the mission lifetime and, once deployed, the devices must withstand this harsh low-Earth environment until re-entry; a process which can take several years. The DAS’ deployable aluminised Kapton sails are particularly susceptible to undercutting by atomic oxygen. In preparation for commercialising the DAS, Cranfield University and Belstead Research Ltd. have submitted several joint proposals to better understand the degradation process of the drag sail materials and to qualify the materials for the specific application of drag sails in low Earth Orbit (LEO). This paper will outline the proposals and the expected benefits from the projects. Additionally, collisions with debris could accelerate the degradation of the system and generate additional debris. This paper will discuss a future ESABASE2 risk assessment study, aiming to quantifying the probability of collisions between the deployed drag sail and orbital debris. The atmospheric models required to simulate the aforementioned risks are complex and often fail to accurately predict performance or degradation observed in the space environment. A previous UKSA Pathfinder project highlighted this issue when different atmospheric models with varying levels of solar activity yielded drastically different re-entry times. Since Cranfield University has two deployed drag sails in orbit, previous de-orbit analysis performed using STELA and DRAMA will be updated and the simulations will be compared to actual data. This paper will conclude in a summation of the different on-going research projects at Cranfield University related to commercialising the DAS family. This research will benefit the wider space community by expanding the understanding of the effects of long-term exposure on certain materials, as well as improving the validity of future low Earth atmospheric models.
Keywords: Atomic Oxygen Undercutting; Aluminised Kapton; Material Degradation; Low Earth Orbit; Drag Sails; Space Debris